Attention deficit Hyperactive Disorders (Adhd) and substance use disorders: overlap, coincidence or fate? - Peters, H.; Abd Rashid, R.; Sulaiman, A.H.; Ahmad Zahari, M.M.; Amer Nordin, A.S.; Robson, Noorzurani; Said, M.A.; Ahmad Adlan, A.; Abdul Rahim, A.; Zakaria, H. (2010)
The link among ADHD and addiction is increasingly shifting into the focus of scientific study. It becomes obvious that ADHD functions as a risk factor and condition for dependence. Disturbances in psychosocial functioning and the tendency towards substance abuse are highly correlated. Objective: This overview relies on a Medline research. Its objective is to describe the joint characteristics among ADHD and addiction. We especially focus on the neurobiological similarities between both diseases. Results: The results of this literature review support the hypothesis of a close genetic, neurological and phenotypic linkage between ADHD and addiction. Furthermore, ADHD often serves as the source for substance abuse disorders among youths and adults. Conclusions: The increasing clinical meaning of the overlap among ADHD and addiction urgently necessitates for consideration regarding preventive planning.